Strategy for Strengthening Work Culture in an Effort to Improve the Quality of Health Services (Case Study at Community Health Center in Tasikmalaya City) - Rr Titie Purwaningsari; Atty Tri Juniarti; Azhar Affandi; Denok Sunarsi (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The purpose of this study is to find out how strategies to strengthen work culture can improve the quality of health services at the Puskesmas. This study used a qualitative method with respondents at the Sangkali Health Center and Panglayungan Health Center in Tasikmalaya City who had measured the quality of health services. Whereas in the Panglayungan Health Center as a comparison Health Center, there are only two work cultures that need to be strengthened, namely professionalism and cooperation. In terms of service quality that has not been achieved, both Puskesmas do not have a Puskesmas quality policy. The Sangkali Health Center still lacks an understanding of quality, while the Panglayungan Health Center already has an understanding of service quality.